Electroacupuncture in rats infected with Strongyloides venezuelensis: Effects on gastrointestinal transit and parasitological measurements - Dos Anjos-Ramos, Luana; Gama, Loyane Almeida [UNESP]; Hauschildt, Andrieli Taise; Fujiwara, Ricardo Toshio; Corá, Luciana Aparecida; Américo, Madileine Francely (SAGE Publications, 2018)
Objective To investigate the effects of electroacupuncture (EA) at ST36 and CV12 on gastrointestinal transit and parasitological measurements during Strongyloides venezuelensis infection in rats. Design Rats were infected with S. venezuelensis and allocated to one of three groups that were infected and remained untreated (SV group, n=8), infected and treated with EA at CV12 (SV+CV12 group, n=8) or infected and treated with EA at ST36 (SV+ST36 group, n=8). EA was performed every 3 days over a 21-day period, at 4 mA intensity and 15 Hz frequency for 20 min. At 2 and 20 days post-infection (dpi), body weight, food and water intake, and faecal characteristics were monitored over a 24-hour period. Gastric emptying, caecal arrival time, small intestinal transit and eggs per gram (EPG) of faeces were calculated at 3, 9, 15 and 21 dpi. At 21 dpi, intestinal worm recovery was counted. Results EA at ST36 and CV12 slowed gastric emptying over the course of infection time. An accelerated intestinal transit was observed in the ST36 group, and after CV12 treatment the same effect was observed at 9 and 15 dpi. At 9 dpi, EPG was increased in the CV12 group. ST36 treatment decreased EPG at 9 and 15 dpi. At 21 dpi, both the ST36 and CV12 groups had increased EPG and worm numbers. No changes were observed in the other parameters analysed. Conclusions EA at ST36 and CV12 provoked changes in gastrointestinal transit that may be beneficial to the host during S. venezuelensis infection; however, based on the number of worms and EPG at 21 dpi, the indication for EA in the treatment of strongyloidiasis needs to be carefully assessed.
Keywords: electroacupuncture; gastrointestinal motility; strongyloidiasis